MODERNIZATION OF THE SYSTEM OF THE MIGRATORY ACCOUNT BY MEANS OF GRADUAL AUTOMATION - Oksana Gennadyevna Orlinskaya (Вестник Северо-Кавказского федерального университета)
The article describes the automated system of migration flows management. Shows the author's position on the automation system of the migratory account.